The Effectiveness of Audio-Lingual Method by Using Wordup Application to Increase Student’s Vocabulary for Eleven Grade of MA Al-Fatah Gondang - Ida Royani; Sahid MA (Metaphor, 2025)
This study aims to improve students’ vocabulary through the use of audio-lingual method by using WordUp application at MA Al-Fatah Gondang in the eleventh grade. The data were collected using a mixed-method approach, including interviews and tests. This study uses an intact-group comparison design where the researcher divides the eleventh grade into two groups, namely the experimental group and the control group. In its application, the experimental group uses the audio-lingual method by using WordUp application while the control group uses other methods and is carried out in one cycle, namely pre-test, treatment, post-test. The results of the study show that the use of the audio-lingual method by using WordUp application can improve students’ vocabulary because this method successfully motivates students to continue learning vocabulary. The audio feature makes students aware that their pronunciation is still lacking and the example sentences in each word help students’ motivation and confidence to continue learning vocabulary. The students’ vocabulary has increased, as shown by test scores from pre-test to post-test. Therefore, the audio-lingual method by using WordUp application are considered effective in improving students’ vocabulary and fostering motivation to learn English.